2011
DOI: 10.4103/0378-6323.79704
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic multicentric reticulohistiocytosis: A clinicopathologic challenge

Abstract: Multicentric Reticulohistiocytosis (MRH) is a rare, systemic non-Langerhans cell histiocytosis (non-LCH) with prominent joint and skin manifestations. It is mostly self limiting. However, 15-30% of the cases are associated with malignancy and carry a poor prognosis. We report the case of a 42-year-old man who presented with multiple reddish-brown papules that on biopsy showed aggregates of oncocytic histiocytes with several multinucleate giant cells. Immunostains were positive for CD 68, CD 45 and were negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Reticulohistiocytosis other than MR are reported to associate almost exclusively with haematological neoplasms (RH‐AHN) in line with what recently highlighted for other histiocytoses . In the international medical literature, fourteen cases of RH‐AHN are described between 1976 and 2018: twelve associated with myeloid neoplasms (including acute and chronic conditions) and two more with lymphoproliferative disorders . All described patients are adult males who display a generalized papular eruption before, concurrently or shortly after the diagnosis of the underline malignancy (Fig.…”
Section: Clinical Findings and Systemic Associationssupporting
confidence: 61%
“…Reticulohistiocytosis other than MR are reported to associate almost exclusively with haematological neoplasms (RH‐AHN) in line with what recently highlighted for other histiocytoses . In the international medical literature, fourteen cases of RH‐AHN are described between 1976 and 2018: twelve associated with myeloid neoplasms (including acute and chronic conditions) and two more with lymphoproliferative disorders . All described patients are adult males who display a generalized papular eruption before, concurrently or shortly after the diagnosis of the underline malignancy (Fig.…”
Section: Clinical Findings and Systemic Associationssupporting
confidence: 61%
“…Intriguingly, no previous cases of reticulohistiocytoses associated with SM have been described so far. On the other hand, the association of reticulohistiocytosis with AML has been reported twice, both cases being middle‐aged males with multiple cutaneous lesions that later developed AML . Specifically, in one previous report, spontaneous involution of the cutaneous lesions occurred as later AML developed, whereas a second case showed persistence of cutaneous reticulohistiocytosis after AML onset.…”
Section: Discussionmentioning
confidence: 99%
“…ovarian cancer, endometrial carcinoma, breast cancer, hepatocellular carcinoma, mesothelioma, malignant melanoma, and urothelial carcinoma) and haematological malignancies . In a subset of such cases, it has been observed that the remission of the associated malignant condition led to an attenuation of the MR manifestations, suggesting that these conditions can be regarded as potential paraneoplastic diseases . Intriguingly, no previous cases of reticulohistiocytoses associated with SM have been described so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Various malignancies including endometrial carcinoma, adenocarcinoma of the gastrointestinal tract, Burkitt lymphoma, liver carcinoma, acute myeloid leukemia, ovarian carcinoma, melanoma, and mesothelioma have been reported. [14][15][16][17][18][19][20] This high rate of association has led to debate of MRH being a paraneoplastic syndrome. However, there is no consistent type of neoplasm associated with MRH, and the two diseases do not always run a parallel course.…”
Section: Abstract Introductionmentioning
confidence: 99%